FORMATION OF A HUMAN CAPITAL DUE TO RAISING OF LIVING STANDARDS - EVIDENCE FROM THE CHUVASH REPUBLIC - Anastasia V. Petrova (Статистика и экономика)
Today the human capital is one of important and specific factors forming high and stable development both a particular region and entire country. Its qualitative formation depends on the impact of different factors, one of which is a society standard of living. Wanting intelligent and significant investments in people the government is unable to establish a high-efficient development of the economy.